A capability approach to evaluating the social impact of music residencies and touring in remote Australia. (19th July 2021) - Howell, Gillian; Bartleet, Brydie-Leigh
Abstract: Evaluation is a driving concern for arts organizations the world over, and a growing requirement from philanthropic, government, and corporate funders. There is increasing recognition of the need for evaluations of socially engaged arts programs to be appropriate for the communities, cultural contexts, participants, and stakeholders involved in their activities. This article directly addresses this need, and outlines the process of developing a bespoke framework for evaluating the social impact of a music program in the Kimberley region of far north-west Australia, a region with a majority First Nations' population. It describes the methods used to develop this evaluation framework and indicators that were grounded in community perspectives on the difference that this music program makes to community life. It situates the methods chosen within a theoretical orientation towards a capability approach and an ecological understanding of externally provided arts activities. The authors argue that this methodology offers a culturally relevant, holistic way to track and measure the direct and indirect outcomes that engagement with the arts can bring.